ОСОБЕННОСТИ ОБРАЗА ТЕКСТА НА РУССКОМ ЯЗЫКЕ - Левченко, Елена (Studia Rossica Posnaniensia, 2008)
The main task of our scientific research was to compare processing the texts in Russian and English languages. In our experiments 210 native Russian speakers were asked to draw “a text in Russian” and after that to draw “a text in English”. The study demonstrates the existence of the mental representations of the text and the culture, the text and the language and the text and the speech. The representation of a Russian text is more positive, detailed, intensive and is closely connected with Russian culture and history (in comparison with the representation of an English text).